Analisis Agenda-setting Policy dalam Proses Penyelenggaraan Formula E di DKI Jakarta - Alfathon, Rivaldi Pradana; Fauzi Said, Mochammad; Ilman Hakim, Andy (Universitas Brawijaya, 2023)
This research aims to analyze studies related to the dynamics of agenda-setting policy in the process of implementing Formula E in DKI Jakarta. This research uses agenda-setting policy theory developed by John W. Kingdon. This research analyzes the interactions carried out by the actors involved in the process of organizing Formula E in DKI Jakarta. The research method used in this research is a qualitative research method. In order to obtain primary research data, researchers interviewed pro and con parties in this research, one of which was the DKI Jakarta Provincial Government and several factions in the Regional People's Representative Council (DPRD) of DKI Jakarta Province. Researchers also use secondary data originating from various mass media and other literature sources. The results of this research show that there is a polemic of pros and cons in the process of holding Formula E in DKI Jakarta. This polemic exists because there are interests from each party. Through political streams, researchers found the formation of coalitions to fight for the respective interests held by various parties. This aims to include these interests so that they can be put at the top of a policy agenda. Political stream is the most dominant aspect in the dynamics of agenda-setting for the Formula E implementation process in DKI Jakarta.